2014
DOI: 10.1016/j.ijosm.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Osteopaths' professional views, identities and conceptions – A qualitative grounded theory study

Abstract: Background: The professional status of osteopathy calls for the critical evaluation of the beliefs, knowledge and conceptions which underlie practitioners' clinical practice. Objectives: To explore experienced osteopaths' professional identities, views and overall conceptions of osteopathy in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Despite the passing of time, most of these osteopathic models have not been updated in response to the evidence, yielding to an uncritical development of the profession [23]. The lack of integration of EBP in osteopathic professional development has been explored across the world, with the subject receiving significant attention in the UK [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the passing of time, most of these osteopathic models have not been updated in response to the evidence, yielding to an uncritical development of the profession [23]. The lack of integration of EBP in osteopathic professional development has been explored across the world, with the subject receiving significant attention in the UK [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, osteopaths, practicing outside of the USA, focus on the diagnosis, treatment, prevention and rehabilitation of musculoskeletal disorders, and the effects of these conditions on a patients’ general health, using predominantly hands-on manual therapy skills [68]. It is worth noting that a range of professional views and identities reside within osteopathy [911], and there is continued debate across the profession globally as to the particular theoretical, philosophical, and evidential underpinnings that define osteopathy and guide clinical practice and reasoning [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there was some indication in our study that participating osteopaths had a misconstrued understanding of the EBP paradigm, with a large proportion of participants believing that EBP did not take into consideration the patient's perspective. Other studies have also indicated that osteopaths view EBP as a threat to the professional identity of the profession [24,25,48]. This suggests that Spanish osteopaths might bene t from revisiting the fundamental purposes of contemporary EBP which seeks to prioritise ethical care, is relationship-based, advocates shared decision-making and relates the evidence to the individual patient's context and situation [7].…”
Section: Ebp Attitudesmentioning
confidence: 99%
“…The lack of integration of EBP in osteopathic professional development has been explored across the world, with the subject receiving signi cant attention in the UK [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%